Revision of the Nearctic Species of the Shore-Fly Genus Scatophila Becker (Diptera: Ephydridae) - Zatwarnicki, Tadeusz; Mathis, Wayne N. (Zootaxa, 2024)
The Nearctic species of the shore-fly genus Scatophila Becker are revised. We treat 26 species of which three are new (type locality noted in parenthesis): Scatophila angusta sp. nov. (Oregon. Baker: Goose Creek (35 km E Baker City; 44°49.2’N, 117°27.79’W; 825 m)), S. bolwigi sp. nov. (Alaska. Valdez-Cordova (Census Area): Gulkana River (19.3 km N Glennallen; 62°16.1’N, 145°23.1’W)), and S. mystacina sp. nov. (Utah. Grand: Green River (15.3 km N; 39°7’N, 110°6.6’W; 1225 m)). Specimens of S. carinata Sturtevant and Wheeler syn. nov. are reported herein to be conspecific with S. tuberculosa Cresson, the latter name having priority. Five species (S. contaminata (Stenhammar), S. cribrata (Stenhammar), S. iowana Wheeler, S. mesogramma (Loew), and S. unicornis Czerny)) are discovered to have Holarctic distributions, especially the Alaskan fauna, and S. contaminata (Stenhammar) is reported for the first time from the Nearctic Region. Emphasis is given to structures of the male terminalia, which are fully illustrated and described. Detailed locality data and distribution maps for included species are provided. For perspective and to facilitate recognition of genera, the tribe Scatellini is diagnosed and a key to genera and species groups from the New World are provided.